Propuesta de lineamientos y protocolos para la validación de los equipos industriales y unidades de procesos ubicados en el centro de servicios industriales (CESI) del centro de procesos e innovación para la industria sostenible de la Universidad de América. (2023)
In this degree project called "proposal of guidelines and protocols for the validation of industrial equipment and process units located in the industrial services center", the main objective is to carry out a preliminary analysis of the equipment that will be located in the CESI (Industrial Services Center) in CEPIIS (Center for processes and innovation for sustainable industry) to subsequently develop the guidelines and protocols for the start-up of the equipment. Four pieces of equipment are located at CESI: the steam generating plant, the wastewater treatment plant, the compressors and special gases.